2019
DOI: 10.1097/sla.0000000000002764
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Telementoring Without Encumbrance

Abstract: The ARHMD system promises to improve accuracy and to eliminate focus shifts in surgical telementoring. Because ARHMD participants were able to refine their execution of instructions, task completion time increased. Unlike a tablet system, the ARHMD does not require modifying natural motions to avoid collisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…Our goal this time was to observe a simple HMD. Previous research that used the HMD reported that their aims included establishing a remote education system of surgical methods [23] and a system using the Oculus Rift to create a simulation or medical VR environment [33]. These studies are considered useful in clinical practice and/or surgery settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our goal this time was to observe a simple HMD. Previous research that used the HMD reported that their aims included establishing a remote education system of surgical methods [23] and a system using the Oculus Rift to create a simulation or medical VR environment [33]. These studies are considered useful in clinical practice and/or surgery settings.…”
Section: Discussionmentioning
confidence: 99%
“…Various head-mounted display (HMD) devices, such as Oculus (Facebook), VIVE (HTC), and Hololens (Microsoft), have been developed and are available in the market today. Moreover, wearable devices such as Google Glass (Google) and Hololens [10,20-23], the usefulness and feasibility of which are being studied, are used for medical purposes. 3D model presentation methods include both monitors and HMDs; nowadays, 3D printers are also employed [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the HMD and built-in screen-based systems was reported in the experiments. Rojas-Munoz et al (2018) found that an AR HMD yielded smaller performance errors and fewer focus shifts in comparison with a telestrator system in which mentees used a nearby screen to retrieve the instructions. Andersen et al (2017) developed a tablet display system similar to an HMD in which a tablet was positioned between the operating field and the local surgeon's head.…”
Section: Overall Systemmentioning
confidence: 93%
“…In 19 (76%) of the experiments, a new AR prototype was developed, while the remaining (6 or 24%) used or modified AR devices developed by a third party. Microsoft HoloLens version 1 (Microsoft, 2019) was used in five experiments (Hanna et al, 2018;Lin et al, 2018;Mitsuno et al, 2019;Rojas-Munoz et al, 2018;Wang et al, 2017), and Google Glass (Google, n.d.) was used in one experiment (Ponce, Menendez et al, 2014).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation